Roitt's essential immunology - Delves, Peter J.; Roitt, Ivan M. (Ivan Maurice) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"Roitt's Essential Immunology - the textbook of choice for students and instructors of immunology worldwide Bringing you fully up-to-date with the latest knowledge and concepts about the workings of the immune system, the hallmark easy-reading style of Roitt's Essential Immunology clearly explains the key principles needed by medical and health sciences students, from the basis of immunity to clinical applications. Beautifully presented, with brand new illustrations, the pedagogy has been strengthened throughout, and includes "just to recap..." sections at the beginning of each chapter, reminding the reader of key findings and principles, and summary sections at the end of each chapter that are ideal for quick study and revision. Also available as a FREE enhanced Wiley Desktop Edition (upon purchase of the book), Roitt's Essential Immunology is supported by a suite of online resources at www.roitt.com including: Interactive MCQs and SBA questions for each chapter, with feedback on all answers selected . Animations and videos showing key concepts. Fully downloadable figures and illustrations, further reading and useful links Extracts from the Encyclopaedia of Life Science Podcasts to reinforce the key principles explained in the text: ideal for revision 'on the go' "--Provided by publisher.
"A new, 12th edition of the definitive Immunology textbook, now fully up-to-date on the latest knowledge and concepts about the workings of the immune system. Essential Immunology is a perfect course textbook to support a series of lectures, or themes, on Immunology: pedagogy has been strengthened throughout, and the text is now fully supported by a suite of online resources as well as a FREE enhanced Wiley Desktop Edition"--Provided by publisher.
Machine generated contents note: Preface. -- Acknowledgements. -- 1. Innate Immunity. -- 2. Specific acquired immunity. -- 3. Antibodies. -- 4. Membrane receptors for antigen. -- 5. The primary interaction with antigen. -- 6. Immunological methods and applications. -- 7. The anatomy of the immune response. -- 8. Lymphocyte activation. -- 9. The production of effectors. -- 10. Control mechanisms. -- 11. Ontogeny and phylogeny. -- 12. Adversarial strategies during infection. -- 13. Vaccines. -- 14. Immunodeficiency. -- 15. Hypersensitivity. -- 16. Transplantation. -- 17. Tumour immunology. -- 18. Autoimmune diseases.
Rev. ed. of: Roitt's essential immunology / Ivan M. Roitt, Peter J. Delves.
Includes bibliographical references and index.
Keywords: Immunology; Immune System; Immunity